DNA Immunization Against Proacrosin Impairs Fertility in Male Mice - García, Lucila (2012)
Problem: Evaluation of proacrosin/acrosin ability to induce an immune response in male mice after genetic immunization and assessment of animal fertility. Method of study: Mice received 50 μg per animal of a plasmid containing the human proacrosin cDNA (pSF2-Acro) (control: empty plasmid, pSF2). The humoral response was evaluated by ELISA and immunocytochemistry. In vivo fertility was assessed by mating immunized males with control females. The effect of antibodies upon Ca +2-ionophore-induced acrosomal exocytosis (AE) and in vitro sperm-zona pellucida (ZP) binding was also studied. Results: pSF2-Acro-immunized mice developed high levels of specific antibodies (P < 0.05) that recognized the sperm acrosomal cap. The number of fertile mice was lower (P = 0.027) in pSF2-Acro-immunized animals than in controls. Litter size was smaller (P < 0.05) in the pSF2-Acro group compared with controls. A negative correlation (P < 0.05) between antibody levels and litter size was found. Antiproacrosin/acrosin antibodies inhibited sperm-ZP binding (P < 0.0001) and Ca +2-ionophore-induced AE (P < 0.05). Conclusion: DNA immunization against proacrosin elicits an immune response in male mice associated with abnormal sperm functions and reduced fertility. © 2012 John Wiley & Sons A/S.